Investigating the feasibility of photogrammetric area-based image matching technique in the measurement of three-dimensional deflections of structures - Mustaffar, Mushairry; Ahmad, Azhar; Sa'ari, Radzuan (Universiti Teknologi Malaysia, 2005)
The study of beam deflections and deformations is one of the many important areas in civil engineering. Designs need to be checked for deflections. The physical behaviour of a structural member subjected to loading provide useful information to structural engineers in deriving optimum designs. Present laboratory practice uses transducers in determining the deflections of beams. These transducers are fitted such that they are physically in contact with the beams. As such, much time is spent in the preparation of the equipment and peripherals for a particular test. Furthermore, deflections can only be measured at points where transducers are fixed and in many cases would be limited. Deflections at any other points, if desired, would be obtained by calculations. This study presents the use of close range digital photogrammetry to obtain a three-dimensional deflections of a concrete beam. Since, photogrammetry has always had the advantage of being able to provide measurements on a large number of points on the object of interest, the representation of the deflections would be enhanced. Image correspondence is achieved by using an area-based image matching which makes use of simple surface models. Laboratory tests involving load test on concrete beams were performed. Images of the beam under various load were captured using off-the-shelf digital cameras that are relatively fixed and calibrated. Whilst the image matching process employs a revised area-based matching algorithm, the image coordinate refinements and the three-dimensional model of the beam surface was acquired through elementary photogrammetric operations. Validation of the results was done by means of comparing the photogrammetric output against those obtained from the transducers. Initial results show that the differences between the photogrammetric and conventional approaches are not statistically significant. This indicates that the use of close-range digital photogrammetry in producing the deflections is a viable additional approach in determining the physical deformities of concrete structures.